The effect of comic strips media towards students' reading comprehension in narrative text (an experimental study at the Tenth Grade Students of SMAN 1 Cijaku in the Academic Year 2023/2024) - Mulyawati, Siti; Ade Sudirman; Tatu Munawaroh (Journal of Contemporary Issues in Primary Education, 2024)
This research paper aim to investigation the effect of comic strips media towards students’ Reading Comprehension in narrative text an experimental study at the Tenth Grade Students’ of SMAN 1 Cijaku. The research paper used the quantitative research design with the characteristics of experimental method that is design into two classes. They are experimental and control class. The population of this research is class X of SMAN 1 Cijaku, they consists 134 students. The sample of this research is X1 as an experimental class consists 33 students and X2 as a control class consists of 35 students. The total of sample is 68 students. The instrument is a test and data of this research are collected by giving pre-test and post-test. The data is analyzed using SPSS version 25.0 program including mean, standard deviation and t-test.  It could be seen from the result of the post-test of experimental and control class. The findings reveal that the data analysis and interpretation of the research, it is clear there is a significant effect of comic strips media towards students’ reading comprehension in narrative text an experimental study at the tenth grade students of SMAN 1 Cijaku.  It can be seen, the minimum score pre-test is 15, maximum is 45, mean 26.14 and standard deviation 7.867. While the minimum score post-test control class is 20, maximum 60, mean 36.43 and standard deviation 9.360. Furthermore, the minimum score of control class is 15, maximum 50, mean 33.64 and standard deviation 8.685. While the minimum score post-test of experimental class is 30, maximum 60, mean 46.06 and standard deviation 8.174. The result of t-test obtained sig. value 0.000 ≤ ??? = 0.05. Ha is accepted and Ho is rejected. It can conclude that there is a significant effect of comic strips media towards students reading comprehension in narrative text.